Microwave assistant synthesis of trans-4-nitrostilbene derivatives in solvent free condition - Cen, Ming Jun; Wang, Yu; He, Yong Wu (European Journal of Chemistry, 2017)
A general method for the synthesis of trans-4-nitrostilbenes has been developed. The trans-4-nitrostilbene could be synthesized in good yields under microwave irradiation within 10 min through Perkin reaction by using 4-nitrophenylacetic acid, benzaldehydes and pyrrolidine.